A promoção da interdisciplinaridade entre a dança contemporânea e as danças urbanas em prol do desenvolvimento técnico-artístico dos alunos dos 8º e 9º anos da Escola de Dança da Companhia de Dança de Almada - Fernandes, Isabella (2023)
ABSTRACT - This internship report aims to reflect upon the foundation, development, and practical application of the Master's program in Dance Education at the Escola Superior de Dança, focusing on the promotion of interdisciplinarity between Contemporary Dance (including Release Technique, Laban/Bartenieff, Humphrey/Limón, and Cunningham Technique) and Street Dance (such as Hip Hop, Popping, House, Waacking, and Locking) in the context of Contemporary Dance Technique classes. The objective is to explore how the principles of Street Dance can assist in teaching Contemporary Dance Technique, fostering, complementing, and reflecting on the teaching of this discipline. The research targets 8th and 9th-grade students in Basic Education (4th and 5th-year students in Specialized Artistic Education) at the Dance School of the Almada Dance Company, aiming to understand, promote, and develop the technical and artistic abilities of these students, aged between 12 and 15 years. From an understanding of the internship context, the report discusses and substantiates the philosophical and methodological process employed by the teacher to promote interdisciplinary dance education. This includes a deep dive into the construction of methodologies within the mentioned Contemporary Dance techniques and the principles of Street Dance. The report then presents the planning and execution of the internship based on the methodological proposal of action research, identifying, and analyzing data collected from observation grids, students' logbooks, and the teacher's field notes, and image recordings to facilitate a qualitative and quantitative analysis and reflection on the artistic practice within this context. The work is grounded in the concept of interdisciplinarity, allowing for reflection on the individual's development through the art of dance, considering these different technical aspects of dance with the aim of connecting the practice and teaching methodologies of dance, using dance to enhance one's own dancing skills.